The association between ischemia modified albumin and placental histopathology in uncomplicated term deliveries. Issue 9 (September 2015) - Kiseli, Mine; Gürsoy, Aslı Yarci; Akincioglu, Egemen; Çağlar, Gamze Sinem; Çandar, Tuba; Demirtaş, Selda
Abstract Ischemia modified albumin (IMA) is a marker of ischemia elevated in different clinical conditions and its use for hypoxia in perinatology is of current interest. We aimed to investigate the association between maternal and cord blood IMA levels and placental histopathological findings in uncomplicated term deliveries. In this study, placental histopathological evaluation in uncomplicated deliveries that ended with healthy newborns revealed 80.6% vasculopathy. The results support the hypothesis that hypoxia exceeding the placental reserve ends with fetal compromise. Moreover, the presence of maternal vasculopathy in placenta is not correlated with maternal and fetal IMA levels.